Correlates of climate change skepticism - Leka, Jona; Furnham, Adrian (Frontiers in Psychology, 2024)
A plethora of research explores the characteristics of environmental attitudes and correlates of climate change beliefs (Hornsey et al, 2016). However, few scholars have attempted to examine climate change beliefs from the denialist perspective. The majority of psychometric tools employed to examine Climate Change Beliefs tend to include items that may skew responses towards more 'alarmist' attitudes. In this study we carried out an investigation of Climate Change beliefs through a new tool constructed from the denialist perspective. The study explored how widespread sceptical beliefs are in Europe and to what extent they are associated worldviews such as Just World Beliefs, Political ideology and attitude aspects, such as Tolerance of ambiguity. We also set out to test the association between Dark Side personality facets and climate change scepticism, a relatively underexplored factor in the climate change attitudes literature. We believe this research, being in the Environmental Psychology, Psychometrics, and Social Psychology fields is within the remit of the Frontiers in Psychology journal.